PENGEMBANGAN MODUL PEMBELAJARAN PADA MATERI METABOLISME DI SMA NEGERI 4 LUBUKLINGGAU PROVINSI SUMATERA SELATAN - Ivoni Susanti (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to understand the importance of metabolis processes in organisms through the development of learning modules for students of SMA Negeri 4 Lubuklinggau. The type of research is development using the Borg and Gall develeopment model which is modified into 4 stages. After validation, the next step is to apply it to clas XII students. The results show that there are differences in student learning outcomes using the modules on fatty acid material and free fatty acid tests between before and after using the module and carrying out experiments, with the average value of the initial test (pre-test) 57,78 smaller than the average values. The final test (post-test) is 80,69 and is greater than the KKM score (70).